Relationship Between Illness Representations, Psychosocial Adjustment, and Treatment Outcomes in Mental Disorders: A Mini Review - Averous, Priscillia; Charbonnier, Elodie; Dany, Lionel (Frontiers in Psychology, 2020)
Understanding and improving the psychosocial adjustments (e.g. quality of life, depression) and treatment outcomes (e.g. adherence, beliefs about treatments) of people with mental disorders is a major health issue. The self-regulation model (SRM) postulates that illness representations play a central role on adjustment and treatment of people with physical illnesses. Recently, the SRM has been used with people with mental disorders. However, the manifestations of somatic and psychiatric disorders can be very different. Therefore, the use of SRM in the field of mental health is very complex. This difficulty, as well as the growing interest for illness representations in the field of mental health, justifies the utility to conduct review on this topic. The current review shows that illness representations are related to psychosocial adjustment and/or treatment outcomes for people with various mental disorders (e.g. psychotic disorders, mood disorder, PTSD, ADHD). However, some limitations to the applicability of SRM to mental disorders have been highlighted. These limitations should be considered in future studies.